Pengaruh Kepuasan Pelanggan Terhadap Keputusan Pembelian Ulang Pada Usaha Air Masak Isi Ulang Asyraf Di Dusun Sempurna Alam - Rivaldi Rivaldi; Arfianti Novita Anwar; Hendry Kurniawan (Journal of Innovative and Creativity, 2025)
The study purpose was to empirically analyze the influence of customer satisfaction on the repurchase decisions of consumers at the Asyraf boiled refill water business, a local UMKM in Dusun Sempurna Alam. In an increasingly competitive market, customer retention is a key factor for business sustainability. This research was prompted by the observation of fluctuating sales data, which suggests that while there is a base of loyal customers, their repurchase behavior is not consistently stable, highlighting the critical need to understand the role of satisfaction in fostering loyalty. Materials and methods. This study utilized a quantitative approach with a causal research design. The sample consisted of 50 customers selected through purposive sampling, with the criterion of having made at least two purchases. Primary data were collected via an online questionnaire distributed through Google Forms, employing a 5-point Likert scale. Data analysis was conducted using simple linear regression after the data successfully passed validity, reliability, and classical assumption tests (normality, multicollinearity, and heteroscedasticity). Results. The findings confirmed a positive and statistically significant effect of customer satisfaction on repurchase decisions. The regression analysis yielded the equation Y = 4.985 + 0.572X. The significance of this relationship was supported by the t-test, which showed a t-value of 10.583, significantly higher than the t-table value of 1.676 at a 0.05 significance level. Furthermore, the coefficient of determination (Adjusted R²) was 0.694, indicating that customer satisfaction accounts for 69.4% of the variance in repurchase decisions. Conclusions. Customer satisfaction is a powerful and essential driver of repurchase decisions within this UMKM context. The study concludes that to build a stable customer base and ensure long-term business viability, the company must prioritize strategies aimed at consistently maintaining and enhancing the customer experience.